Influence of pressure of working atmosphere on the formation of phase-structural state and physical and mechanical properties of vacuum-arc multilayer coatings ZrN/CrN - Sobol, O. V.; Andreev, A. A.; Gorban, V. F.; Stolbovoy, V. A.; Meylekhov, A. A.; Postelnyk, A. A.; Dolomanov, A. V. (My University, 2016)
For multilayer coating system ZrN/CrN determined the effect of the pressure of the working atmosphere of nitrogen (Pɴ), DC (˗Us) and pulse (-Ui) negative bias potential during the deposition and the thickness of the layers in the period on the phase composition, texture, substructural characteristics and physical-mechanical properties. It is found that for Рɴ = (2.2...12)·10-4 Torr in the layers of chromium nitride formed on a lower nitrogen phase with the β-Cr2N simple hexagonal crystal lattice, and in the zirconium nitride layers are formed of a stoichiometric ZrN phase with a cubic lattice. Such a multilayer coating (layer thickness about 50 nm) at the maximum in this range Pɴ = 1.2·10-3 Torr is most solid (39 GPa) with a modulus of elasticity of 268 GPa and the ratio H/E = 0.145. At higher Pɴ, when the layers are formed phase stoichiometric composition with homogeneous crystal lattices (ZrN and СrN) hardness of the composition is not more than 33 GPa. The mechanisms of the effects observed are based on the higher barrier properties of the interphase boundary layers with different types of crystal lattices was discussed.

Для багатошарових покриттів системи ZrN/CrN визначено вплив тиску робочої азотної атмосфери (PN), постійного (-Us) і імпульсного (-Ui) негативних потенціалів зсуву при осадженні, а також товщини шарів у періоді на фазовий склад, текстуру, субструктурні характеристики і фізико-механічні властивості. Встановлено, що при PN = (2,2...12)·10-4 Торр у шарах нітриду хрому формується нижча по азоту фаза β-Cr2N з простою гексагональною кристалічною решіткою, а в шарах нітриду цирконію відбувається формування стехіометричної фази ZrN з кубічною решіткою. Таке багатошарове покриття (товщина шарів близько 50 нм) при найбільшому з цього інтервалу PN = 1,2·10-3 Торр є найбільш твердим (39 ГПа) з модулем пружності 268 ГПа і співвідношенням H/E = 0,145. У випадку більш високих PN, коли в шарах відбувається утворення фаз стехіометричного складу з однотипними кристалічними решітками (ZrN і СrN), твердість композиції не перевищує 33 ГПа. Обговорено механізми спостережуваного ефекту, що засновані на більш високих бар'єрних властивостях міжфазної межі шарів з різними типами кристалічних решіток.
Вплив тиску робочої атмосфери на формування фазово-структурного стану і фізико-механічні властивості вакуумно-дугових багатошарових покриттів ZrN/CrN
Keywords: pressure of nitrogen atmosphere; impulses; hardness; mechanical properties; імпульси; структурна інженерія; кристалічні решітки; осадження